Memory and trauma in international relations : theories, cases and debates - Resende, Erica Simone Almeida.; Budryte, Dovile. (Interventions (Routledge (Firm)), 2014)
"This work seeks to provide a comprehensive and accessible survey of the international dimension of trauma and memory and its manifestations in various cultural contexts"--